Predicted Value of MicroRNAs, Vascular Endothelial Growth Factor, and Intermediate Monocytes in the Left Adverse Ventricular Remodeling in Revascularized ST-Segment Elevation Myocardial Infarction Patients - Del Toro, Raquel; Galeano-Otero, Isabel; Bevilacqua, Elisa; Guerrero-Márquez, Francisco; Falcon, Debora; Guisado-Rasco, Agustín; Díaz-de la Llera, Luis; Barón-Esquivias, Gonzalo; Smani, Tarik; Ordóñez-Fernández, Antonio (Frontiers in Cardiovascular Medicine, 2022)
Background: PPCI in patients with STEMI improves the survival of patients. Nevertheless, some patients develop LVAR. The main objective is to find reliable prognostic biomarkers for left ventricular adverse remodeling (LVAR) in patients with ST-segment elevation myocardial infarction (STEMI). We aimed to characterize the role of pro-inflammatory cell populations, related cytokines and microRNAs (miRNAs) released after Primary percutaneous coronary intervention (PPCI). Methods: We assessed the level of pro-inflammatory subsets, before and after the revascularization, 1 and 6 months after the PPCI, using flow cytometry. We also performed miRNAs microarray in isolated peripheral blood mononuclear cells (PBMCs) and examined the levels of 27 cytokines in patients’ serum by multiplex ELISA. Results: We observed that levels of classical and intermediate monocytes were increased 6 hours after PPCI in patients who developed LVAR. Multivariate regression analysis and ROC curves indicated that the level of intermediate monocytes, after PPCI, was the best monocyte subset that correlated with LVAR. In addition, we observed that the increase in the level of vascular endothelial growth factor (VEGF) correlated with LVAR. Furthermore, we found significant increase in levels of miR-16, miR-21-5p, and miR-29a-3p, 6 hours post-PPCI in LVAR patients. We determined that the combined level of intermediate monocyte subpopulation, VEGF and miRNAs were highly associated with LVAR, and the combined ROC analysis provided high accurate specificity and sensibility to identify STEMI patients who will develop LVAR. Conclusion: Our data suggest that the combined analysis of intermediate monocytes, VEGF and miRNAs might predict reliably LVAR in STEMI patients.